Retirement, intergenerational time transfers, and fertility - Peter Eibich; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Retired parents might invest time into their adult children by providing childcare. Such intergenerational time transfers can have important implications for family decisions. This paper estimates the effects of parental retirement on adult children's fertility. We use representative panel data from Germany to link observations on parents and adult children. We exploit eligibility ages for early retirement for identification in a regression discontinuity design. The results show that parent's early retirement significantly increases the probability of childbirth for adult children. However, parental retirement affects only the timing of adult children's fertility, without having an effect on total fertility.
Keywords: J13; J14; J22; J26; 330; Retirement; fertility; intergenerational transfer; time use